Differential splicing and glycosylation of Apoer2 alters synaptic plasticity and fear learning - Wasser, Catherine R. (Sci Signal, 2014)
Apoer2 is an essential receptor in the central nervous system that binds to the apolipoprotein ApoE. Various splice variants of Apoer2 are produced. We showed that Apoer2 lacking exon 16, which encodes the O-linked sugar (OLS) domain, altered the proteolytic processing and abundance of Apoer2 in cells and synapse number and function in mice. In cultured cells expressing this splice variant, extracellular cleavage of OLS-deficient Apoer2 was reduced, consequently preventing γ-secretase-dependent release of the intracellular domain of Apoer2. Mice expressing Apoer2 lacking the OLS domain had increased Apoer2 abundance in the brain, hippocampal spine density, and glutamate receptor abundance, but decreased synaptic efficacy. Mice expressing a form of Apoer2 lacking the OLS domain and containing an alternatively spliced cytoplasmic tail region that promotes glutamate receptor signaling showed enhanced hippocampal long-term potentiation (LTP), a phenomenon associated with learning and memory. However, these mice did not display enhanced spatial learning in the Morris water maze, and cued fear conditioning was reduced. Reducing the expression of the mutant Apoer2 allele so that the abundance of the protein was similar to that of Apoer2 in wild-type mice normalized spine density, hippocampal LTP, and cued fear learning. These findings demonstrated a role for ApoE receptors as regulators of synaptic glutamate receptor activity and established differential receptor glycosylation as a potential regulator of synaptic function and memory.